POLITICAL COMMUNICATION AND ITS INNOVATIVE ROLE IN THE LIFE OF SOCIETY - Babaev Tolibjon Abdujalilovich (European Journal of Humanities and Educational Advancements, 2023)
This scientific article analyzes the category of political communication, its theoretical and practical aspects. Different stages, directions and methods of manifestation of political communication are revealed. Separately, the role of communication skills in the conditions of political modernization in the life of society and the state has been studied. Based on the collected and analyzed sources, scientifically substantiated conclusions are made